Evidence of two mobile amorphous phases in semicrystalline polylactide observed from calorimetric investigations. Issue 5 (25th July 2013) - Delpouve, Nicolas; Arnoult, Mickael; Saiter, Allisson; Dargent, Eric; Saiter, Jean‐Marc
<x xml:space="preserve">Abstract</x> Amorphous phase dynamics in Poly(lactic acid) (PLA) with different crystallinity degrees have been investigated from the vitreous state to the glass transition by means of two calorimetric methods. Temperature Modulated Differential Scanning Calorimetry was used to characterize the heat capacity signals and the average cooperativity length at the glass transition in non‐aged materials. Standard DSC was used to study the physical aging. It is shown that amorphous and fully crystallized PLA exhibit different relaxation parameters. For semicrystalline PLA with an intermediate degree of crystallinity, the peaks of the enthalpy of recovery and the out‐of‐phase heat capacity component are bimodal. The bimodality of the peaks is attributed to the relaxations of the inter‐spherulitic and intra‐spherulitic amorphous phases, respectively. Thus, in partially crystallized PLA, the non‐crystalline fraction of the material could be divided in three fractions, namely the Rigid Amorphous Fraction, the inter‐spherulitic Mobile Amorphous Phase (MAP), and the intra‐spherulitic MAP. Each of them exhibits a distinct molecular mobility. POLYM. ENG. SCI., 54:1144–1150, 2014. © 2013 Society of Plastics Engineers